Species Sorting and Neutral Theory Analyses Reveal Archaeal and Bacterial Communities Are Assembled Differently in Hot Springs - Li, Lianwei; Ma, Zhanshan (Sam) (Frontiers in Bioengineering and Biotechnology, 2020)
Although the recognition of archaea as one of the three kingdoms in the tree of life has been nearly a half-century long, the comparative investigations on their ecological adaptations with bacteria have been limited. The mechanisms of their community assembly and diversity maintenance in the hot spring have not been studied. The mechanistic study is critical not only for understanding the hot-spring microbiome structure and dynamics, but also for shedding light on their evolutionary adaptations. We applied neutral model and species sorting of metacommunity theory to investigate how hot-spring microbial communities were assembled, how their diversities were maintained, and how the temperature and pH influence these mechanisms. We found that: (i) Archaeal and bacterial communities are assembled differently, with stochastic neutral force play a more significant role in archaeal communities than in bacterial communities (neutrality-rate=52.9% vs. 15.8%, p-value<0.05). (ii) Temperature and pH account for rather limited (<10%) variations in hot-spring microbiomes. The pH has more significant influence than temperature on archaeal communities, and both pH and temperature have similarly low influences on bacterial community structure. (iii) The differences between archaea and bacteria are most likely due to the longer evolutionary history and better adaptation of archaea to host spring environments.